Assessing the quality of retrofits in solid wall dwellings. Issue 5 (13th November 2017) - Glew, David; Smith, Melanie B.; Miles-Shenton, Dominic; Gorse, Christopher
Abstract : Purpose: The purpose of this paper is to provide a detailed appraisal of the quality of domestic retrofits. Design/methodology/approach: This paper presents the results of technical surveys on 51 retrofits undertaken before, during and after the retrofits. Findings: Failures are observed to be endemic and characterised into five themes: 72 per cent showed moisture issues pre-retrofit, 68 per cent had moisture risks post-retrofit, 62 per cent did not adopt a whole house approach, 16 per cent showed inadequate quality assurance protocols and 64 per cent showed evidence of insufficient design detailing. Each theme is further subcategorised with a view to identifying implications for future policy. Research limitations/implications: The findings suggest the 10 per cent Ofgem retrofit failure rates predictions are an underestimate and so there may be a need for additional investigations to understand the trend across the UK. Practical implications: Recommendations to reduce the failure rates may include making changes to the current inspection regime, widening understanding among installers; providing standard repeatable designs for repeated features; and empowering occupants to trigger inspections. Social implications: The sample is representative of a substantial proportion of the homes in the UK suggesting that retrofit quality may in many instances be below the required standards. Originality/value: Risks of moisture issues and underperformance in domestic retrofit are a concern for government industry and households. This research shows that many installation failures are the result of not implementing existing guidelines and a change to the enforcement of standards may be needed to enact a fundamental change in installer practice and process control.